The Effect Of Sales Growth And Company Size On Profitability (Study On Food Sub-Sector Companies On The Indonesia Stock Exchange For The 2019-2021 Period): (Studi Pada Perusahaan Sub Sektor Makanan di Bursa Efek Indonesia Periode 2019-2021) - Latief Z Nur; Eli Achmad Mahiri (Institute of Computer Science (IOCS), 2022)
Companies with good performance will be able to achieve the goals to be achieved by the company, namely maximizing the value of the company. This goal can be achieved by increasing the company's profitability. This study was conducted with the aim of testing the effect of sales growth and company size on profitability in food industry companies on the Indonesia Stock Exchange during the 2019-2021 period. The data used were secondary data and the number of population was 18 companies, the research sample was taken on the basis of purposive sampling. The sample criteria that meet as many as 11 companies while the analysis technique used is panel data regression analysis with the help of the Eviews 9.0 program to obtain a comprehensive picture of the relationship between one variable and another. The results of the analysis prove that the sales growth variable has no significant effect on profitability, company size has a significant effect on profitability